Imaging swallowing function and the mechanisms driving dysphagia in inclusion body myositis - Salam, Sharfaraz; Allen, Jodi; Dimachkie, Mazen M; Hanna, Michael G; Machado, Pedro M (Clinical and experimental rheumatology, 2024)
Sporadic inclusion body myositis (IBM) is a progressive condition which commonly affects patients aged above 40. IBM does not respond to immunosuppression and no proven treatments are available. Up to 80% of patients develop some degree of swallowing impairment during the disease course. Dysphagia is a source of marked morbidity in IBM and predisposes patients to life-threatening complications such as aspiration pneumonia. The pathophysiology behind dysphagia in IBM is not fully understood. Evidence from imaging demonstrates that impaired swallowing is predominantly underpinned by oropharyngeal deficits. Changes in cricopharyngeal physiology is thought to be an important factor influencing dysphagia in IBM. However, it is unclear whether this is secondary to structural changes within the cricopharyngeus itself or driven by impairment of the muscles promoting pharyngeal clearance. The approach to dysphagia in IBM patients is limited by a lack of validated instruments to reliably assess swallowing function and an absence of effective therapeutic interventions derived from controlled trials targeting dysphagia. Imaging modalities such as the video fluoroscopic swallowing study (VFSS) are commonly used to evaluate dysphagia in IBM. Whilst VFSS is a commonly used technique in clinical practice; cumulative radiation exposure with repeated testing can be a limitation. Alternative imaging techniques could be developed further as outcome measures for assessing swallowing.In this review, we provide an overview of imaging techniques used to assess swallowing and the insight provided from such investigations into the mechanisms behind dysphagia in IBM. We suggest future directions for evaluation and outcome measurement of dysphagia in this population.